2017
DOI: 10.1002/arch.21445
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and functional assay of a fatty acyl‐CoA reductase gene in the scale insect, Ericerus pela Chavannes (Hemiptera: Coccoidae)

Abstract: Ericerus pela Chavannes (Hemiptera: Coccoidae) is an economically important scale insect because the second instar males secrete a harvestable wax-like substance. In this study, we report the molecular cloning of a fatty acyl-CoA reductase gene (EpFAR) of E. pela. We predicted a 520-aa protein with the FAR family features from the deduced amino acid sequence. The EpFAR mRNA was expressed in five tested tissues, testis, alimentary canal, fat body, Malpighian tubules, and mostly in cuticle. The EpFAR protein was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 28 publications
0
17
0
Order By: Relevance
“…EpFAR) are reported to be involved in cuticular wax biosynthesis. 7,8,10 Thus, we conclude that despite the high homology, the biological functions of FARs within groups are not conserved during insect evolution.…”
Section: Phenotype I: Somementioning
confidence: 76%
See 3 more Smart Citations
“…EpFAR) are reported to be involved in cuticular wax biosynthesis. 7,8,10 Thus, we conclude that despite the high homology, the biological functions of FARs within groups are not conserved during insect evolution.…”
Section: Phenotype I: Somementioning
confidence: 76%
“…9 EpFAR, which was identified in the wax-producing Ericeru pela, was shown to be involved in wax biosynthesis by reducing acyl CoA to its corresponding alcohol. 8 In our previous study, we identified a FAR (NlFAR7) displaying a periodical expression peak in the integument of the brown planthopper Nilaparvata lugens after each molting. NlFAR7 is involved in the synthesis of CHCs and plays a crucial role in insect cuticle waterproofing.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…While more than 20 FARs have been experimentally characterized from 23 moth and butterfly (Lepidoptera) species 25 , FARs from other insect orders have received far less attention. Single FAR genes have been isolated and experimentally characterized from Drosophila (Diptera) 14 , the European honeybee (Hymenoptera) 26 and the scale insect Ericeus pela (Hemiptera) 27 . Our limited knowledge about FAR function prevents us from drawing inferences about the biological significance of the FAR gene family expansion in insects.…”
Section: Introductionmentioning
confidence: 99%